1994
DOI: 10.2337/diacare.17.4.267
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Two Measures of Quality of Life in Patients With Type I and Type II Diabetes

Abstract: This study provides evidence for the reliability and validity of two measures of quality of life. The two measures examine quality of life from different but complimentary perspectives. The DQOL seems more sensitive to lifestyle issues and contains special questions and worry scales oriented toward younger patients, whereas the SF-36 provides more information about functional health status. Thus, the measures may be used usefully in combination in studies of both type I and type II diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
307
3
25

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 435 publications
(369 citation statements)
references
References 0 publications
34
307
3
25
Order By: Relevance
“…Our results are consistent with other studies that have demonstrated lower health-utility scores in women with diabetes [6,[31][32][33] and worse QoL in the presence of complications [6,20,33,34]. However, even with inclusion of gender and diabetic complications in the model, frequency of hyperglycemic symptoms was associated with lower health-utility scores.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with other studies that have demonstrated lower health-utility scores in women with diabetes [6,[31][32][33] and worse QoL in the presence of complications [6,20,33,34]. However, even with inclusion of gender and diabetic complications in the model, frequency of hyperglycemic symptoms was associated with lower health-utility scores.…”
Section: Discussionsupporting
confidence: 92%
“…The better the acceptance of the disease, the more effective the patient's performance, not only in relation to accession to control of blood glucose. [22][23][24][25] Groups that present low acceptance of the disease also present inadequate control of blood glucose. The level of acceptance of the patient with diabetes and situations related to their routine have a direct influence on blood glucose levels and adherence to treatment.…”
Section: Resultsmentioning
confidence: 99%
“…However, diabetic complications (especially macrovascular diseases) and other comorbid illnesses seem to deteriorate HRQL measured by SF-36 among type II diabetes patients. [12][13][14][15][16][17] One randomised intervention study showed that regular phone contacts with the patients improved glycaemic control but did not induce any improvement in HRQL measured by SF-36. 36 Another study showed that by achieving good glycaemic control (HbA1c from 10.4 to 7.8% during 1 y follow-up) and by losing hyperglycaemic symptoms, the patients gained HRQL benefits especially in PF, vitality, and HC since last year.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Weight loss achieved by surgical techniques 1 and lifestyle interventions [4][5][6][7][8][9][10][11] has improved HRQL. Diabetes with its complications has been associated with deteriorated HRQL [12][13][14][15][16] and improvement in glycaemic control with the loss of hyperglycaemic symptoms has improved HRQL in type II diabetes patients. 17 Sibutramine, a norepinephrine and serotonin reuptake inhibitor enhances satiety 18,19 and results in sustained weight loss in obese patients.…”
Section: Introductionmentioning
confidence: 99%